Embedded Pragmatic Trials in Dementia Care: Realizing the Vision of the NIA IMPACT Collaboratory. (26th June 2020) - Mitchell, Susan L.; Mor, Vincent; Harrison, Jill; McCarthy, Ellen P.
Abstract : Close to 6 million Americans have Alzheimer's disease (AD) or Alzheimer's disease and related dementia (AD/ADRD). These high‐need, high‐cost patients are vulnerable to receiving poor quality uncoordinated care, ultimately leading to adverse health outcomes, poor quality of life, and misuse of resources. Improving the care of persons living with dementia (PLWD) and their caregivers is an urgent public health challenge that must be informed by high‐quality evidence. Although prior research has elucidated opportunities to improve AD/ADRD care, the adoption of promising interventions has been stymied by the lack of research evaluating their effectiveness when implemented under real‐world conditions. Embedded pragmatic clinical trials (ePCTs) in healthcare systems have the potential to accelerate the translation of evidence‐based interventions into clinical practice. Building from the foundation of the National Institutes of Healthcare Systems Collaboratory, in September 2019 the National Institute on Aging Imbedded Pragmatic AD/ADRD Clinical Trials (IMPACT) Collaboratory was launched. Its mission is to build the nation's capacity to conduct ePCTs within healthcare systems for PLWD and their caregivers by (1) developing and disseminating best practice research methods, (2) supporting the design and conduct of ePCTs including pilot studies, (3) building investigator capacity through training and knowledge generation, (4) catalyzing collaboration among stakeholders, and (5) ensuring the research includes culturally tailored interventions for people from diverse backgrounds. This report presents the rationale, structure, key activities, and markers of success for the overall NIA IMPACT Collaboratory. The articles that follow in this special Issue describe the specific work of its 10 core working groups and teams. J Am Geriatr Soc 68:S1–S7, 2020 .